2018
DOI: 10.2460/javma.253.10.1294
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of elective gonadectomy procedures performed on dogs and cats by veterinary students and shelter veterinarians in a shelter environment

Abstract: OBJECTIVE To determine complication rates for elective gonadectomy procedures performed by veterinary students on dogs and cats in an animal shelter, characterize these complications, and compare rates with those for shelter-employed veterinarians (SEVs). DESIGN Retrospective cohort study. ANIMALS 10,073 dogs and cats for which gonadectomy was performed by a veterinary student (n = 3,048 surgeries) or SEV (7,025 surgeries) at an urban animal shelter over a 16-month period. PROCEDURES Electronic medical records… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 16 publications
2
8
0
Order By: Relevance
“…This is a potential limitation of the data described in this report as the cases reported to have been performed primarily by a resident-intraining likely had differing levels of faculty supervision. There are various reports in the veterinary literature addressing the difference in surgical complications related to the experience of the clinician (31)(32)(33). These reports generally support the finding described here that the complication rate following surgical procedures is not significantly increased when performed by resident-in-training veterinarians.…”
Section: Discussionsupporting
confidence: 84%
“…This is a potential limitation of the data described in this report as the cases reported to have been performed primarily by a resident-intraining likely had differing levels of faculty supervision. There are various reports in the veterinary literature addressing the difference in surgical complications related to the experience of the clinician (31)(32)(33). These reports generally support the finding described here that the complication rate following surgical procedures is not significantly increased when performed by resident-in-training veterinarians.…”
Section: Discussionsupporting
confidence: 84%
“…Traditionally, universities have focused their shelter medicine educational research on surgical skills gained on rotation. While there is validated benefit in these surgical experiences ( 28 , 31 , 39 ), this study indicates that there are more experiences in shelter medicine education that students find deeply fruitful which warrant further investigation. This is especially evident considering students spend roughly 1/3 of their time on the rotation performing surgery, yet it was the 19th most common mention in our journal entries.…”
Section: Discussionmentioning
confidence: 79%
“…Research has shown that experiences in shelter medicine can increase perceived self-confidence and preparedness for real-world challenges in the field post-graduation ( 31 ) and increase self-confidence in various shelter medicine themes ( 29 ). These experiences have also been shown to increase student rating of their ability to perform six shelter medicine tasks as well as ovariohysterectomy/ovariectomy (OVH/OE) and castration surgeries ( 31 ), and decreased surgery time ( 28 , 38 ) without a significant increase in complication rates ( 39 ). This finding of decreased surgery time without a significant increase in complication rates is further corroborated by studies in human medicine that have shown no difference between trainees and more-experienced surgeons in postoperative complication rates when careful patient selection and close supervision of trainees is applied ( 40 42 ).…”
Section: Introductionmentioning
confidence: 99%
“…33,48 Shelter medicine programs pose little risk to the animals; a recent study demonstrated that the risk of complications for cats and dogs undergoing sterilization procedures in a shelter setting was similar between student surgeons and employed veterinarians. 50 Shelter medicine programs also offer the potential for high volume experience; one program reported that fourth-year students averaged 65 sterilization surgeries over a 2-week period with a notable decrease in surgical time. 48 The shelter surgery program added an average of 9000 small animal cases annually.…”
Section: Where and How Can Surgery Be Taught?mentioning
confidence: 99%
“…Students gain valuable experience in numerous core competencies that prepare them for their career, making them better prepared to meet employer expectations 33,48 . Shelter medicine programs pose little risk to the animals; a recent study demonstrated that the risk of complications for cats and dogs undergoing sterilization procedures in a shelter setting was similar between student surgeons and employed veterinarians 50 …”
Section: Where and How Can Surgery Be Taught?mentioning
confidence: 99%